The Problem of Archaeographical Research in Tartar Science Sphere - Мишкинене, Галина (Acta Orientalia Vilnensia, 2003)
This article analyses the latest archaeographical research in the field of Lithuanian Tatar written manuscript heritage. The author gives her answer to the question: was the work of fixing, collecting and description of Lithuanian Tatar manuscripts purposeful. The main emphasis is put on the work stage and its specific character.Archaeography has not always fulfilled tasks equally throughout different historical periods starting with Lithuanian Tatar written language presentation to wide academic society (Fleischer 1838, Muchlinskij 1858) and up to nowadays. While catalogization of manuscripts existed (1935, 1961, 1968, 1997, 2000 and 2003), it was not purposeful since “field archaeography” had been omitted. The publication of complete texts was ascribed to episodical (2000, 2001).Urgency of catalogization and description of manuscripts was based on changes of the situation inside society and also outside it. Nowadays manuscripts in Tatar families are rarity. Because the social and political situation has changed, the approach to this treasury is weakly controlled. Purposeful archaeographical research could assist in saving Lithuanian Tatar cultural heritage and also to analyse it from many perspectives.